Tindak Tutur Ekspresif Dalam Kolom Komentar Youtube Kok Bisa? Mengenai “Seberapa Bahaya Vape Sebenarnya?” - Sukesih, Sri; Ningsih, Rika (UIR Press, 2026)
The objective of this study is to identify the expressive speech acts used in the comment section of the